Wastewater reuse in Turkey: from present status to future potential - Nas, Bilgehan; Uyanik, Sinan; Aygün, Ahmet; Doğan, Selim; Erul, Gursel; Nas, K. Batuhan (Iwa Publishing, 2020)
The Ministry of Environment and Urbanization (MoEU) initiated an important project, 'Reuse of Treated Wastewater in Turkey', in 2017. With this project, all wastewater treatment plants (WWTPs) were investigated to determine wastewater reuse purposes for the first time. The results obtained from this project were that although there are 1,015 existing WWTPs, only 15 of them realized wastewater reuse. In 2017, the total volume of reused treated wastewater in Turkey amounted to 29.6 million m(3)/year, accounting for 0.78% of the treated urban wastewater. With the present water potential and sectoral water use rates, Turkey should make key administrative and technical regulations in the coming years for water reuse. This paper aims to give an overview of wastewater reuse activities from present status to future potential in Turkey and the opportunities and challenges in expanding water reuse. The status of WWTPs, treatment processes and their compliance with the WWTPs where reuse is carried out in Turkey are evaluated in this study. The realization of the planned goals and challenges are discussed after regulatory changes in Turkey for reclaimed wastewater and reuse targets for 2023.
Keywords: advanced treatment; reclaimed water; wastewater; wastewater regulations; water reuse